Manure composition from Kansas swine lagoons - Keeler, G.L.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Analysis of 41 manure samples from Kansas swine lagoons revealed that nutrient concentrations were higher than previously reported values from the Nebraska Cooperative Extension Service and the Midwest Planning Service. In addition, high standard deviations indicated that considerable variation exists in composition of waste in swine lagoons. Although means from some lagoons were lower, most producers had manure that analyzed higher than previously published values from other sources. These data reveal the imnportance of individual analysis of lagoons for proper application to cropland to maximize yield and environmental stewardship. Additional research needs to be completed to provide a more detailed understanding of nutrient concentrations from manure samples in Kansas.
Keywords: Swine; Swine lagoons; Maure; Environment